GAJAH DALAM KARYA SENI LUKIS BATIK - Resta Dwi Puzi; Erwin Erwin (Universitas Negeri Padang, 2020)
This final work aims to visualize the life of an elephant is getting worse. There are several stages in the embodiment methods of this work, namely: preparation, elaboration, synthesis, concept realization, and completion. Elephants in the form of realist style batik painting. The author managed to create 10 works with the titles: dryness, trapped, tortured, arid, lost, exhausted, extinct 1, extinct 2, misery, survival. This work recommended to appreciatiative and artist, next to more realizing about safe the habitat of the Elephants in order to no extinct.Keywords: Elephant, Batik Painting, Realist Style